A hierarchical overlay network optimisation model for enhancing data transmission performance in blockchain systems - Longle Cheng; Haibo Tan; Xiru Li; Wansu Pan; He Zhao; Munan Yuan; Xiaofeng Li (Scientific Reports)
Abstract The network layer plays a crucial role in blockchain systems, enabling essential functions such as message broadcasting and data synchronization. Enhancing data transmission structures and methods at this layer is key to improving scalability and addressing performance limitations. Currently, the uneven distribution of neighboring node lists and the lack of awareness of underlying linkages in coverage networks hinder the efficiency and comprehensiveness of information transmission. To tackle these challenges, this study introduces a dual-layer transmission model, FPSblo-EP, which divides the blockchain P2P network into two layers: the regular node layer and the tagged node layer. In the initial stage, network nodes are treated as points in a point cloud, and farthest point sampling is applied to the P2P network nodes. During this process, geographic distances between nodes serve as input parameters, while node degrees are used as point weights. Tagged nodes can then provide efficient and stable inter-group routing for regular nodes, creating a hierarchical transmission architecture. This model improves both transmission performance and scalability in blockchain overlay networks. Experimental results show that FPSblo-EP reduces message coverage latency by 22%, redundancy by 26%, and the network stretch coefficient by 28%, demonstrating superior load-balancing capabilities and enhanced network reliability.